Interfaces and Software Control Models of Multipoint Aerial Objects Trajectory Measurements System - Tevyashev, A. D.; Koliadin, A. (Друкарня Мадрид, 2020)
This paper is devoted to the development of the software interfaces for multipoint air objects trajectory measurements system.
Keywords: aerial objects tracking; user interface; multi-threading; cross-platform; signals and slots; performance